PENGARUH MOTIVASI DAN BUDAYA KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI BIRO AUPK UIN AR-RANIRY BANDA ACEH - Nelliraharti Nelliraharti; Murnia Suri (Universitas Ubudiyah Indonesia, 2019)
AbstractMotivation and working culture are factors affecting work productivity of employee. The purpose of this research was to know the influence of the motivation and working culture on work productivity of AUPK bureau employees of UIN Ar-Raniry Banda Aceh. The method used in this research was descriptive method with quantitative approach. The techniques of data collection used in this research were scale questionnaire and documentation. The population of this research was employees working at AUPK bureau employees of UIN Ar-Raniry Banda Aceh consisting of 116 people. The technique of data analysis was statistic analysis. The result of this research showed that (1) rate of influence between work motivation of the employees and the work productivity was 0.672. The influencing factors could be viewed from internal factor, for example, responsibility in implementing task, the poses of goals, the availability of feedback; and external factor, such as the fulfill of life needs, the willing of earning praise, expect of obtaining financial incentive, calling attention of friends and superiors. The contribution of variable X1 towards Y was 45.16 percent and the rest, 54.84 percent, was determined by another variable. (2) The influence rate between working culture and work productivity of the employees was 0.450. The influencing factor could be viewed from behavior on working hours, sense of responsibility for the work, the carefulness and frugalities in doing the work, the strong will to conducted the duty and help each other. Meanwhile, the contribution of variable X2 towards Y was 20.35 percent and the rest, 79.75 percent, was determined by the other variables. (3) The contribution rate influence simultaneously between X1 and X2 towards Y, 0.712, was strong category, and the contribution the variable X1 and X2 towards Y was 50.6 percent and the rest, 49.4 percent, was determined by the other variables. Keywords: Motivation, Working Culture, Work Productivity